Luminance distribution modifies the perceived freshness of strawberries. (2012)
Material perception studies focus on the analysis of visual cues that may underlie the ability to distinguish between the different properties of an object. Herein, we investigated the effects of luminance distribution on the perceived freshness of a strawberry independent from its colour information. We took photographs of the degradation of a strawberry over 169 hours in a controlled environment, then presented cropped square patches of the original images to subjects who then rated the perceived freshness using a visual analogue scale. Freshness ratings were significantly highly correlated with statistical measures of the luminance and colour channels. To clarify which of these visual cues affects freshness perception, we created artificial images by modifying only the luminance distribution and keeping the colour information unchanged. The modification of luminance resulted in a highly correlated change in freshness perception, suggesting that luminance visual cues are essential to the freshness perception of strawberries. Finally, by eliminating the colour information from the images, we examined the contribution of luminance distribution independent of colour information and found that luminance information suffices for accurate estimation of strawberry freshness.